2004
DOI: 10.1097/01.prs.0000091163.86851.9c
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of the Extensor Tendons to the Fingers over the Dorsum of the Hand: A Study of 50 Hands and a Review of the Literature

Abstract: The extensor tendons to the fingers were studied in dissections of 50 fresh cadaveric hands, and the divisions of the tendons, as well as the communications (juncturae), were analyzed. The pattern of distribution most frequently observed was as follows. The extensor digitorum communis provided one tendon to the index finger, one to the middle finger, two to the ring finger, and none to the little finger. The extensor indicis exhibited one tendon, whereas the extensor digiti minimi exhibited two tendons. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
67
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 10 publications
8
67
0
6
Order By: Relevance
“…In the present study it was present in all the specimens, but was single in 45.7% and doubled in 54.3% of specimens. A tendon slip from the extensor digiti minimi to the ring finger was observed in one hand was reported by Zilber & Oberlin [9]. Mehta V et al [16] reported that a case of accessory tendon of EDM merging proximally with extensor carpi ulnaris.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present study it was present in all the specimens, but was single in 45.7% and doubled in 54.3% of specimens. A tendon slip from the extensor digiti minimi to the ring finger was observed in one hand was reported by Zilber & Oberlin [9]. Mehta V et al [16] reported that a case of accessory tendon of EDM merging proximally with extensor carpi ulnaris.…”
Section: Discussionmentioning
confidence: 98%
“…Satya Prasad Venugopal [8] reported 2 tendons of EI bilaterally. Extensor indicis was absent in both hands of one cadaver was reported by Zilber & Oberlin [9]. Extensor indicis permit independent extension of index finger and in most commonly used in tendon transfer [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[4][5][6][7][8]10 According to Abu-Hijleh, "No clinical or surgical cases of such occurrence have been reported and therefore it is doubtful whether an accurate estimate of the prevalence of EDM can be made." 2 However, Pfeiffer 11 discovered an EDM while operating on the hand of a 28-year-old patient.…”
Section: Discussionmentioning
confidence: 99%
“…Other anatomic variants of the EIP include absence, duplication, or with anomalous insertions to the thumb, the ring finger, or, more often, the middle finger [25]. The incidence of EIP absence was reported around 1-4 % in a literature review [7,18,27]. In the setting of anomalous anatomy that precludes EIP transfer, we may use an PL tendon transfer.…”
Section: Discussionmentioning
confidence: 99%